Using phenology data to improve control of invasive plant species: A case study on Midway Atoll NWR. Issue 1 (14th May 2020) - Taylor, Robert V.; Holthuijzen, Wieteke; Humphrey, Ann; Posthumus, Erin
Abstract: 1. Restoration of degraded lands often depends on knowledge of invasive plant species' ecology coupled with well‐timed treatments to control them. Little is known about the reproductive phenology of Verbesina encelioides (golden crownbeard), which is a highly invasive annual forb species at Midway Atoll National Wildlife Refuge (NWR). Efforts to control V. encelioides on Midway Atoll NWR were challenging, especially when targeted plants went to seed before being treated. 2. To obtain this information, we documented the timing of key reproductive life cycle events in cohorts of V. encelioides plants on Midway Atoll NWR for 12 months beginning in August 2016; we visited these plants every 3–7 days and noted which phenophases the plants exhibited. 3. We found that it took an average of 76 days for V. encelioides to transition from leaves to seed drop, although the time required varied across the year (range: 31–175 days). Accordingly, invasive plant control schedules were adjusted to re‐treat infested areas every 30 days. 4. By incorporating phenology information into invasive plant control operations at Midway Atoll NWR, efforts to eradicate V. encelioides will have a higher chance of succeeding. Standardized methods, such as those from the USA National Phenology Network, provided useful tools for optimizing the timing of management practices; moreover, these data may help to better inform management of invasive plant species with regard to restoration efforts at a global scale. Abstract : Verbesina encelioides (Golden crownbeard) is a highly invasive annual forb species at Midway Atoll National Wildlife Refuge (NWR), which is the world's largest albatross colony. Past control efforts have been impeded by a lack of biological information about this invasive plant species. Here, we document the success of incorporating phenology information into invasive plant control operations at Midway Atoll NWR, ensuring that efforts to eradicate V. encelioides will have a higher chance of succeeding.